2018
DOI: 10.14701/ahbps.2018.22.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of laparoscopic cholecystectomy in elderly patients after preoperative assessment and optimization of comorbidities

Abstract: Backgrounds/AimsEarly laparoscopic cholecystectomy is considered as the standard treatment of acute cholecystitis. However, whether this procedure is desirable in elderly patients with acute cholecystitis is not clearly elucidated. In this study, we aimed to evaluate the effects of thorough preoperative assessment and consultation for complications on clinical outcomes in elderly patients over 65 and over 80 years.MethodsWe retrospectively analyzed 205 patients who were diagnosed with acute cholecystitis betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
13
1
Order By: Relevance
“…There were no significant differences regarding cardiovascular complications between the four age-groups. Similar findings are also encountered by Shin et al [ 38 ]. With the pre-operative optimization of comorbidities and medications and addressing frailty in a multi-disciplinary team, an experienced surgical staff with good technical equipment are effective in improving postoperative outcomes [ 16 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There were no significant differences regarding cardiovascular complications between the four age-groups. Similar findings are also encountered by Shin et al [ 38 ]. With the pre-operative optimization of comorbidities and medications and addressing frailty in a multi-disciplinary team, an experienced surgical staff with good technical equipment are effective in improving postoperative outcomes [ 16 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings are also encountered by Shin et al [ 38 ]. With the pre-operative optimization of comorbidities and medications and addressing frailty in a multi-disciplinary team, an experienced surgical staff with good technical equipment are effective in improving postoperative outcomes [ 16 , 38 ]. Moreover, the multivariate analysis showed that severe inflammation (gangrenous cholecystitis) and comorbidities such as diabetes, previous stroke and chronic renal and pulmonary disease, but not age itself, are risk factors for postoperative morbidity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Peri-inflammatory conditions in the abdomen induce pathological and molecular changes in the brain [1-4]. Brain uptake of circulating lipopolysaccharide (LPS) is not sufficient to cross the brain-blood barrier (BBB) that most effects of peripherally administered LPS are mediated through LPS receptors located outside the BBB [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have demonstrated the advantages of perioperative outcomes of early cholecystectomy in elderly and younger patients, several of them showed no difference in postoperative morbidity or mortality [ 5 , 6 ]. A recent meta-analysis of systematic review has shown that careful selection of elderly patients contributes to a better perioperative outcome, but there is no uniform guidance on selection or preoperative assessment [ 7 ].…”
mentioning
confidence: 99%